Evaluation of Diabetes Self-Management among Patients in Baghdad City: A Comparative Study - Khalifa, Al-Hakam; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2018)
Objective(s): To Evaluate Diabetes self –management among patients in Baghdad City and to comparebetween these patients self-management relative to the type of the disease.Methodology: A descriptive design was conducted in Baghdad city, started from November 16th 2017 to theend of May 17 th 2018 in order to evaluate Diabetes self-management. Purposive (non-probability) sample,which was consisted of (120) patients who were diagnosed with D.M. The sample is comprised of (60) patientwith diabetes type I and (60) patient with diabetes type II. It is consisted of (60) male and (60) female. Aquestionnaire is constructed for the purpose of the study. It is composed of (42) items. Reliability and validity ofthe questionnaire is determined through pilot study. Data are collected through the use of the questionnaire andthe structured interview as means of data collection. Data are analyzed through the application of descriptivestatistical data analysis approach of frequency, percentage, mean, range and total scores and inferentialstatistical data analysis approach of t-test.Results: The results show that more than a half have a poor level of diabetes self-management (n = 64; 53.3%)and a lesser proportion who have a good level of such management.Recommendations: Further study can be conducted on subjects with a large sample size. An educationprogram can be done to improve patient knowledge about the diabetes self-management. Better attention can bedirected for patients who were students, married and low income ones